Attitude and Tenacity: Which One Mostly Affects Students’ Mathematics Achievement? - Falenthino Sampouw; Elsa Apriska; Totok Victor Didik Saputro; Sri Winarti; Jailani Jailani (PAEDAGOGIA, 2024)
This survey study aims to describe the simultaneous impact of students’ attitude towards mathematics and tenacity towards learning achievement and the partial effect of students’ attitude towards mathematics and tenacity on learning achievement in mathematics. The population of this research was the students of 11th students of public school in Ngaglik, Yogyakarta, Indonesia with 122 students as sample selected by simple random sampling technique. The data collection of students’ attitudes towards mathematics and tenacity were obtained using Likert-scale questionnaire. The questionnaires used in this study are valid and reliable. The data was analyzed using parametric statistics, which was multiple regression. The research results show that: 1) there was significant simultaneous impact on students’ attitude towards mathematics and tenacity towards mathematics learning achievement; 2) there was no significant impact given by students’ attitude towards mathematics learning achievement; 3) there was significant impact given by tenacity towards mathematics learning achievement. Implication and suggestion would be discussed in discussion part